2016
DOI: 10.1007/s40091-016-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural performance of notch damaged steel beams repaired with composite materials

Abstract: An experimental program and an analytical model using ANSYS program were employed to estimate the structural performance of repaired damaged steel beams using fiber reinforced polymer (FRP) composite materials. The beams were artificially notched in the tension flanges at mid-spans and retrofitted by FRP flexible sheets on the tension flanges and the sheets were extended to cover parts of the beams webs with different heights. Eleven box steel beams, including one intact beam, one notch damaged beam and nine n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The numerical modelling is based on an experimental study by El-Taly [17]. Therefore, the design of steel hollow sections remains similar.…”
Section: Design and Specificationsmentioning
confidence: 99%
“…The numerical modelling is based on an experimental study by El-Taly [17]. Therefore, the design of steel hollow sections remains similar.…”
Section: Design and Specificationsmentioning
confidence: 99%
“…Their results indicated that this damage causes decreasing the maximum load of the intact beam from 200 to 106 kN. Shaat (2007) and Eltaly (2016) completely cut the bottom flanges of wide beams and box beams, respectively, at midspan to simulate a severe section loss in the steel beams. Shaat (2007) concluded that the flexural strength and stiffness of the girders was reduced by 60 and 54%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Shaat (2007) concluded that the flexural strength and stiffness of the girders was reduced by 60 and 54%, respectively. Eltaly (2016) indicated that the strength of notched beam was dropped by 34%. Tavakkolizadeh and Saadatmanesh (2001) estimated the effect of partial cutting of the tension flange using different depths of the cut (shallow and deep).…”
Section: Introductionmentioning
confidence: 99%